Revitalizing Islamic Ethics Toward Parents and Teachers in the Grade 10 Aqidah Akhlaq Curriculum - Fangsuri, Fatich Ya'i; Muniron (FITRAH: International Islamic Education Journal, 2026)
This study examines the construction of Islamic ethics concerning respect for parents and teachers in the chapter "Living Honorably by Respecting Parents and Teachers" in the Grade 10 Aqidah Akhlaq textbook for Madrasah Aliyah, developed in accordance with the Indonesian Ministry of Religious Affairs Decree No. 183 of 2019, and explores its relevance to the revitalization of character education. The study employed a qualitative library research approach. The primary data source was the textbook, while secondary data were drawn from scholarly literature on Islamic ethics, character education, and Islamic education. Data were collected through document analysis and analyzed using qualitative content analysis supported by theoretical triangulation. The findings demonstrate that Islamic ethics is constructed through the integration of three interrelated dimensions: faith (Iman), knowledge (ilm), and practice (amal). Faith provides the normative foundation through the Qur'an and the Hadith, knowledge develops moral understanding through the interpretation of religious texts and scholarly perspectives, and practice actualizes these values through respectful conduct toward parents and teachers. Based on these findings, the study proposes the Faith–Knowledge–Practice (Iman–Ilm–Amal) Integration Model as its primary conceptual contribution, explaining how moral character is formed through the interrelationship among theological foundations, intellectual understanding, and ethical practice. The proposed model enriches the discourse on Islamic character education and provides a conceptual framework for revitalizing character education in Islamic educational institutions.